Pendampingan Rehabilitasi Terumbu Karang di Pulau Gili Labak dengan Aplikasi Bioreeftek dari Limbah Batok Kelapa (Cocos Nucifera) - Qomariyah, Adinda Nuril; Putri, Aprilia; Rahmaniah, Siti; Ning Asih, Eka Nurrahema (Jurnal Ilmiah Pangabdhi, 2023)
The high interest of tourists in coral reef snorkeling activities on Gili Labak Island has resulted in considerable damage to the coral reef ecosystem and has the potential to reduce the income of the people of Gili Labak. The purpose of this activity is to provide understanding, outreach, and practice of coral reef rehabilitation using the bioreeftec method from coconut shell waste to tourists and local residents on Gili Labak Island. The realization of this counseling activity was carried out by referring to the root of the problems experienced by the coastal communities of Gili Labak Island, including: 1) The local coastal community has not been educated in preserving the coral reef ecosystem for the continuation of snorkeling tourism activities, 2) The low level of awareness of tourists regarding behavior that threatens the existence of coral reefs during snorkeling activities, 3) There is no concern from the local government regarding the provision of instructions and prohibitions on tourist activities that have the potential to damage coral reefs on the island of Gili Labak. An alternative solution to the problem is conducting counseling activities and coral reef rehabilitation practices on Gili Labak Island using the bioreeftec method from coconut shell waste. The results of coral reef rehabilitation counseling activities on Gili Labak Island showed that as many as 89% of the people of Gili Labak Island were interested in rehabilitating coral reefs to preserve the coral reef ecosystem on the island.